Enantioselective total synthesis of pyrrolo-[2, 1-c][1, 4]-benzodiazepine monomers (S)-(−)-barmumycin and (S)-(+)-boseongazepine B. Issue 16 (10th July 2018) - Bhosale, Viraj A.; Waghmode, Suresh B.
Abstract : An efficient enantioselective total synthesis of pyrrolo-[2, 1- c ][1, 4]benzodiazepine (PBD) monomers ( S )-(−)-barmumycin and ( S )-(+)-boseongazepine B was achieved through a stereocontrolled strategy, which relies on a proline catalysed asymmetric α-amination and ester α-ethylenation. Abstract : An efficient enantioselective total synthesis of pyrrolo-[2, 1- c ][1, 4]benzodiazepine (PBD) monomers ( S )-(−)-barmumycin and ( S )-(+)-boseongazepine B and collective formal total syntheses of oxoprothracarcin, prothracarcin and ( S )-(+)-boseongazepine C are described. The present approach is based on an efficient construction of an ethylidene substituted C-4 pyrrolidine core, that is the stereocontrolled introduction of a trisubstituted double bond through simple enolate α-alkylation of an ester, which also relies on a proline catalysed asymmetric α-amination followed by HWE olefination. The present synthetic route possesses superior stereocontrol over the C-4 ethylidene substituent as well as the C-( S ) stereogenic center, which allows more functional variations on the five-membered prolinol core as compared to the existing PBD synthesis.